Do leaf lignin content or leaf mass-to-area bias the estimation of intrinsic water use efficiency from leaf bulk δ 13 C? A test with seedlings from five oak species - Hana Ghouil; Béatrice Richard; Pierre Montpied; Erwin Dreyer; Oliver Brendel (Annals of Forest Science, 2024)
Abstract Key Message Leaves of seedlings from five oak species (Quercus robur L.; Q. pubescens L.; Q. suber L.; Q. afares Pomel; Q. ilex L.) displayed large, mainly inter-specific, differences in leaf mass-to-area ratio (LMA) and lignin content, as well as in the 13C composition of bulk leaf biomass. The variation in leaf lignin content and LMA did not impact the offset between the 13C composition measured in bulk leaf material versus soluble sugars. This observation, as well as the similar correlations between intrinsic leaf water use efficiency and the 13C compositions of bulk material or soluble sugars extracted from leaves, confirms their reliable use as a proxy for the former even when there is a large variation in LMA or lignin among samples. Context Carbon isotope composition (δ 13 C) of bulk leaf biomass is frequently used as a proxy for intrinsic water use efficiency (iWUE) in large-scale intra- and inter-specific comparisons. However, post-photosynthetic 13C discrimination during the synthesis of lignin combined with differences in leaf mass-to-area ratio (LMA) may bias the relationship between δ 13 C of bulk leaf matter and iWUE and thus its use as a proxy of iWUE. Aims To quantify the impact of differences in lignin content and LMA on the relationship between δ 13 C of bulk leaf biomass and iWUE over a large gradient of lignin contents across five oak species (deciduous: Quercus robur, Q. pubescens, Q. afares and evergreen: Q. ilex and Q. suber). Methods We measured lignin content, LMA, and δ 13 C of bulk leaf biomass and of soluble sugars extracted from the leaves, as well as intrinsic water use efficiency (derived from leaf gas exchange) in seedlings of the five oak species grown under common conditions in a greenhouse and measured in a climate chamber. Results There was a large range (mainly across species) in lignin content (4 to 33%) and LMA (60–180 g m−2). δ 13 C of bulk leaf biomass and soluble sugars were tightly correlated, showing a significant mean offset of − 0.4‰. This offset was stable across species and not correlated to the lignin content of the leaves. A very loose correlation was found between the offset and LMA, mainly due to one species. Conclusion Our results are a demonstration that potential variations in leaf lignin content or LMA have no or only a little effect on the δ 13 C of bulk leaf biomass. They are unlikely to cause a bias when using bulk leaf δ 13 C as a proxy for variations in intrinsic water use efficiency among Mediterranean and temperate broad-leaf forest tree species.